Architectures émergentes à El Alto (Bolivie): essai d’interprétation sociologique - Poupeau, Franck (Environnement urbain / Urban Environment)

(untitled) (Institut National de Recherche Scientifique Centre Urbanisation Culture et Société, 2015)
This article applies Bourdieu’s analysis of the formation of the “scholastic habitus” in medieval times, elaborated in his 1967 afterword to his French translation of Erwin Panofsky’s Gothic Architecture and Scholasticism (2005 [1967]), to a different historical case and social context, namely the correspondence between indigenous mental categories and architectural efflorescence in a city of the contemporary Andes: El Alto. This same principle of homology between mental categories and building layout (rooted in a common habitus) can be used to interpret one of the most spectacular characteristics of “emerging architectures” known as chalets in Bolivia. The term chalet designates a hybrid structure consisting of a penthouse and storey dwelling built on the rooftops. The chalets are architectural forms embedded within an economy of symbolic goods characterized by a “dual truth”: they are at once material and symbolic; they perform economic functions while at the same time seeking conspicuous exposure and public visibility. The hypothesis developed here is that the conspicuous lifestyle revealed by the construction of chalets on the rooftops can be understood by reference to the emerging social power of the indigenous (cholos) elites. This article thus identifies in the fraternities of El Alto the structural equivalent of the scholastic institution that Bourdieu associated with Gothic architecture, in order to reveal the formation of a specific habitus, shared among urban categories defined by similar residential locations, economic activities and forms of collective organization.